Dampak Pelatihan Pemasaran Digital Terhadap Penjualan Produk Lokal di Pedesaan Desa Larike - Fibryano Saptenno; Aziz Laitupa; Jani Jani; Selvenco Tuasuun (Jurnal Kabar Masyarakat, 2024)
The digital marketing training held in Larike Village aims to enhance the community's ability to utilize digital technology as a tool for marketing local products. Desa Larike has significant potential in local products, such as agricultural produce and handicrafts, but still faces challenges in marketing, which is limited to the local area. By leveraging digital technology, local entrepreneurs in the village are expected to expand their market reach and significantly increase the sales of local products. This community service program involves a series of training sessions covering the fundamentals of digital marketing, such as the use of social media, e-commerce platforms, and brand identity management strategies. The people of Desa Larike are taught how to create effective marketing campaigns through social media platforms like Instagram and Facebook, as well as how to manage business transactions via digital platforms. This approach aims to equip the community with skills that can be directly applied to their everyday economic activities. The results of this training show that participants have gained a better understanding of digital marketing and its application in their businesses. Some local entrepreneurs in the village have started using social media and e-commerce platforms to market their products, resulting in an increase in demand from a broader market, not only from local consumers but also from outside the village. This demonstrates the positive impact of the training on local product sales.